Robust metallic microcapsules : a direct path to new multifunctional materials - Sun, Dawei (2021)
Robustness of microcapsule shells determined the service life and application areas of final smart materials including self-healing composites, anticorrosion coatings, smart concretes, and so on. Herein, we designed and synthesized metal microcapsules by conducting electroless plating directly on liquid droplet surfaces, and metal shells showed superior stability in thermal (600 °C) and polar solvents (acetone and N,N-dimethylformamide) environments. More interestingly, the mechanical strength of metal shells was ten times higher than those of all published microcapsules. Besides, the smart epoxy composites remained stable mechanical properties with metal microcapsule concentrations, and this is the first time to report such results. For engineering materials, mechanical properties played an important role in practical applications, and a higher strength usually accompanied with better safety and longer service life. The microcapsules with designable structures could be synthesized by adjusting shell thickness and core fractions for practical requirements. The metal microcapsules had great potentials to be applied in a smart metallic matrix, conductive multifunctional materials, and pH-responsive materials. In addition, the electroless plating technique was also first applied to liquid surfaces pushing the development of novel smart materials.